Anatomical meniscus construct with zone specific biochemical composition and structural organization. (October 2019) - Bahcecioglu, G.; Bilgen, B.; Hasirci, N.; Hasirci, V.
Abstract: A PCL/hydrogel construct that would mimic the structural organization, biochemistry and anatomy of meniscus was engineered. The compressive (380 ± 40 kPa) and tensile modulus (18.2 ± 0.9 MPa) of the PCL scaffolds were increased significantly when constructs were printed with a shifted design and circumferential strands mimicking the collagen organization in native tissue (p < 0.05). Presence of circumferentially aligned PCL strands also led to elongation and alignment of the human fibrochondrocytes. Gene expression of the cells in agarose (Ag), gelatin methacrylate (GelMA), and GelMA-Ag hydrogels was significantly higher than that of cells on the PCL scaffolds after a 21-day culture. GelMA exhibited the highest level of collagen type I ( COL1A2) mRNA expression, while GelMA-Ag exhibited the highest level of aggrecan ( AGG) expression (p < 0.001, compared to PCL). GelMA and GelMA-Ag exhibited a high level of collagen type II ( COL2A1) expression (p < 0.05, compared to PCL). Anatomical scaffolds with circumferential PCL strands were impregnated with cell-loaded GelMA in the periphery and GelMA-Ag in the inner region. GelMA and GelMA-Ag hydrogels enhanced the production of COL 1 and COL 2 proteins after a 6-week culture (p < 0.05). COL 1 expression increased gradually towards the outer periphery, while COL 2 expression decreased. We were thus able to engineer an anatomical meniscus with a cartilage-like inner region and fibrocartilage-like outer region. Graphical abstract: Image 1